2023
DOI: 10.3390/rs15204950
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Potential of Oil Spill Monitoring in a Port Environment Using Optical Reflectance

Bikram Koirala,
Nicholus Mboga,
Robrecht Moelans
et al.

Abstract: In this work, we studied the potential of the visible, near-infrared, and shortwave infrared wavelength regions for monitoring oil spill incidents using optical reflectance. First, a simple physical model was designed for accurate oil thickness and volume estimation using optical reflectance. The developed method was made invariant to changes in acquisition and illumination conditions. In the next step, an algorithm based on an artificial neural network was designed to detect spilled oil. The training samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Various studies have explored oil spill detection using different sensing instruments [ 16 ]. For instance, Koirala et al conducted experiments to examine the potential of using an RGB camera mounted on a drone for the detection of various oil types, including diesel oil and hydraulic oil [ 17 ]. Thomas et al demonstrated the efficacy of combining an infrared Convolutional Neural Network (CNN) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have explored oil spill detection using different sensing instruments [ 16 ]. For instance, Koirala et al conducted experiments to examine the potential of using an RGB camera mounted on a drone for the detection of various oil types, including diesel oil and hydraulic oil [ 17 ]. Thomas et al demonstrated the efficacy of combining an infrared Convolutional Neural Network (CNN) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%